Women Moving Within Borders: Gender and Internal Migration dynamics in Ghana - Awumbila, M. (Ghana Journal of Geography, 2015)
Internal migration is an inherent part of the processes of development and structural transformation in any region. In Africa, while the focus is often on international migration, internal migration is far more significant for development in terms of the numbers of people moving and their poverty reduction potential and well-being outcomes. In Ghana, as the numbers of women and girls moving independently has been on the increase, a “feminisation” of migration is said to be underway. Many of these young women and girls move independent of their families from rural agricultural communities in the north to urban centres in the south, where they work in low scale, mostly unskilled occupations. Despite the increasing numbers of Ghanaian women on the move as internal migrants, and their gendered implications, very few studies have focused on how the relationship between migration and human development operates in gender differentiated ways, nor on how gender as a social construction that organizes relations between males and females can greatly differentiate the causes, processes and impacts of migration on development thereby enhancing economic growth and reducing poverty. Using mainly secondary data, this paper provides an overview of the gendered nature of internal migration movements in Ghana and discusses how gender relations and gendered power dynamics can significantly affect all aspects of the migration process both at area of origin and destination. It also highlights the policy implications of these gendered dynamics. Its central argument is that people's experiences of gender are central to the patterns, causes and impacts of migration and that gender affects how people are able to contribute to and benefit from the migration process and enhance social and economic development. It also urges the need for a more positive and nuanced view and response to rural-urban migrants by Government policies and strategies to enhance the potential benefits of migration for men and women
Keywords: Migration; gender; remittances; migrant livelihoods; informal sector